Capacity Building UMKM Pesisir Melalui Diversifikasi Olahan Ikan Lokal Untuk Peningkatan Nilai Tambah Produk Sebagai Upaya Pencegahan Stunting Di Desa Binaan Politeknik Negeri Jember, Desa Puger Kulon, Kabupaten Jember - Yohan Yuanta; Dessya Putri Ayu; Putri Rahayu Ratri; Surya Dewi Puspita; Dina Fitriyah; Miftahul Jannah; Heri Warsito (STIKES Columbia Asia Medan, 2025)
Puger Kulon Village, located in Puger District, Jember Regency, is a coastal area in East Java with significant marine and fisheries potential. Most of the population earns their living as fishermen and small-scale fishery product processors (MSMEs). Unfortunately, the capacity of MSMEs in this area is still very limited, both in terms of technical skills and product variety. Processed fish products produced by the community are mostly shrimp paste and shredded fish. This community service activity aims to increase knowledge and additional skills for coastal MSMEs regarding the diversification of local processed fish products by encouraging the development of various processed fish products as an effort to increase product added value such as fish nuggets, fish balls, fish dumplings, and fish dim sum. The method used is counseling and technical training with direct practice in diversifying various fish products (fish nuggets, fish balls, dumplings, and fish dim sum). Evaluation was carried out using a pretest and posttest approach on 20 MSME participants using a knowledge assessment instrument. The results showed an increase in knowledge regarding fish processing diversification, with an average score of 74 before the training, increasing to 93 after the training, a 27% increase. Thus, the extension and training on fish processing diversification have proven effective in increasing the knowledge and skills of coastal MSMEs. This activity has the potential to improve the quality and diversity of local fish-based products, while strengthening the role of MSMEs in providing nutritious food from local potential as an effort to prevent stunting in coastal communities.